THE DYNAMIC LANDSCAPE OF MEDICINE: ADVANCEMENTS, CHALLENGES, AND FUTURE HORIZONS - Khamidova S.A. (Scholar Express Journal, 2023)
This article explores the dynamic and transformative nature of contemporary medicine, focusing on key advancements such as genomic medicine, immunotherapy, artificial intelligence, and telemedicine. It discusses the impact of these innovations on diagnostics, treatment strategies, and healthcare accessibility. Additionally, the article addresses challenges in medicine, including ethical considerations and global health disparities. Looking forward, it emphasizes the promising future of medicine, featuring nanotechnology, gene editing, and integrative approaches to healthcare.
Keywords: Dynamic landscape; advancements; challenges